The Association Between Brachial Ankle Pulse Wave Velocity and Left Ventric Mass Index In Patients With Hypertension - Budi Susetyo Pikir (Journal of Global Pharma Technology, 2016)
Background: Arterial stiffness has been considered as a modest method in detecting the arterial burden that can trigger left ventricular hypertrophy in the heart. Increased left ventricle hypertrophy in hypertension patients is a predictor which has impact in the increase of morbidity and mortality. Objectives: We aimed to investigate the association between brachial ankle pulse wave velocity (BaPWV) and left ventricle mass index (LVMI) in patients with hypertension. Material and Methods: This study was conducted by collecting secondary data of 40 hypertension patients aged >40 years old, suffered from hypertension >1 year and have encountered brachial ankle pulse wave velocity test and echocardiography test. Results: There was a significant positive correlation between brachial ankle pulse wave velocity and left ventricle mass index in hypertension patients with r = 0.493 dan p = 0.001. Also, there was a significant correlation between BaPWV and Relative Wall Thickness with r = 0.404 and p = 0.01. There was a significant difference of LVMI value in males and females with the result of (117.78+22.70 and 100.15+16.82, p = 0.008). In contrast, there was no significant difference in BaPWV value in males and females (1865.63+322.29 and 1811.08+350.28). It was also obtained a significant correlation between age factor and systolic blood pressure with LVMI and BaPWV (r = 0.493, p = 0.001). Conclusions: There was significant positive correlation between BaPWV and LVMI in hypertension patients. The arterial stiffness was an indicator of increased left ventricle mass index in hypertension patients.Keywords: Brachial ankle pulse wave velocity, Left ventricle mass index, Hypertension, Heart.